When they call you a terrorist : A black lives matter memoir - Khan-Cullors, Patrisse, 1984-; Davis, Angela (New York : Macmillan Audio, 2018)
A memoir by the co-founder of the Black Lives Matter movement explains the movement's position of love, humanity, and justice, challenging perspectives that have negatively labeled the movement's activists while calling for essential political changes.
Unabridged.
Narrator: Angela Davis.
Requires OverDrive Listen (file size: N/A KB) or OverDrive app (file size: 182398 KB).
Adult.
SORA audiobook.
Keywords: African American Nonfiction; Electronic books; Khan-Cullors, Patrisse, -- 1984-; Black lives matter movement; African American women -- Biography -- Juvenile literature; Women -- Biography; African Americans -- Biography -- Juvenile literature; Autobiographies; SORA audiobook